Telopathes magna gen. nov., spec. nov. (Cnidaria: Anthozoa: Antipatharia: Schizopathidae) from deep waters off Atlantic Canada and the first molecular phylogeny of the deep-sea family Schizopathidae - Macisaac, K. G.; Best, M.; Brugler, M. R.; Kenchington, E. L.r.; Anstey, L. J.; Jordan, T. (Zootaxa, 2013)
A new genus and species of deep-sea antipatharian, Telopathes magna gen. nov., spec. nov., is described from the western North Atlantic off the coast of Canada. Five additional paratypes, consisting of juvenile to adult forms, are reported from the New England and Corner Rise Seamounts (NW Atlantic). Preliminary sequencing of a subsection of the nuclear ribosomal cistron confirmed the phylogenetic affinity of T. magna to the order Antipatharia, and in particular the family Schizopathidae. Subsequent sequencing of three mitochondrial DNA segments from nine of the 11 currently-recognized genera within the Schizopathidae revealed a well-supported phylogenetic relationship between T. magna and Stauropathes. This is the first study to use molecular techniques to elucidate the evolutionary relationships of the Schizopathidae, a family of black corals almost exclusively found in the deep sea (depths >200 m). Telopathes is distinguished from other genera within the family Schizopathidae by its largely pinnulated stalk, sparse branching pattern to the second degree that is not restricted to a single plane, two anterolateral rows of long, simple primary pinnules, arranged alternately to sub-opposite, and colony with an adhesive base. This record of T. magna brings the total number of nominal species of Antipatharia reported to occur off eastern Canada to 12 and represents the third new genus added to the Schizopathidae since a critical review of the family by Dennis Opresko in 2002.